Pendidikan Karakter Analisis Pemikiran Ibnu Miskawaih - Fitriani Rahayu (Al-Mudarris, 2019)
Character education is a important thing to be instilled in school-age children given the many moral crises that have occurred among teenagers lately. In addition to, Indonesia lacks figures who can be used as a role model. That done because many public figures commited the crimes such as corruption, collusion, prostitution, and so on. Ibnu Miskawaih is one of the Islamic philosophers who touches on the concept of character education in his book tahzib al-akhlak wa tahir al-a'raf. By literature studies, this paper attempts to describe the concept of character education offered by Ibnu Maskawaih, namely The Golden(The Doctrin of The Mean). He stated that human character is built from four foundations, namely restraint, courage, wisdom, and justice. The character values developed by Ibnu Maskawaih can be used as a reference for the implementation of education in Indonesia. The expected values or characters are the formation of personality based on the norms of religion, culture and ethics of the Indonesian nation. So, the thought of Ibn Miskawaih is so suitable for using in morality crisis era.